Effect of BI Rate, Non-Performing Finance and Inflation in Return on Assets of Islamic Banking in Indonesia: Effect of BI Rate, Non-Performing Finance and Inflation in Return on Assets of Islamic Banking in Indonesia - Farhadi Arifiansyah (STEI Kanjeng Sepuh Gresik Jawa Timur, 2020)
This study was conducted using a quantitative method with secondary data obtained from the website of Bank Indonesia and the Financial Services Authority. The data used is a time series data from January 2011 to December 2016. Data were analyzed using classical assumption test consisting of: (a) Normality Test; (b) Test of autocorrelation; (c) Test Multicolinearity. Further statistical tests were used consist of; (a) Test t; (b) Test F. Based on these results we concluded as follows: (a) BI Rate partial and insignificant positive effect on Return On Assets; (b) Non-performing finance partial and insignificant negative effect on Return On Assets; (c) Inflation partially negative and not significant Return On Assets. So it can be concluded that the variable BI Rate and Inflation only slightly affect the operational risk while the Islamic Bank non-performing finance considerable influence because of the bad loans directly influence revenue Islamic Bank.